Voice modulation: from origin and mechanism to social impact. (20th December 2021) - Leongómez, Juan David; Pisanski, Katarzyna; Reby, David; Sauter, Disa; Lavan, Nadine; Perlman, Marcus; Varella Valentova, Jaroslava
Abstract : Research on within-individual modulation of vocal cues is surprisingly scarce outside of human speech. Yet, voice modulation serves diverse functions in human and nonhuman nonverbal communication, from dynamically signalling motivation and emotion, to exaggerating physical traits such as body size and masculinity, to enabling song and musicality. The diversity of anatomical, neural, cognitive and behavioural adaptations necessary for the production and perception of voice modulation make it a critical target for research on the origins and functions of acoustic communication. This diversity also implicates voice modulation in numerous disciplines and technological applications. In this two-part theme issue comprising 21 articles from leading and emerging international researchers, we highlight the multidisciplinary nature of the voice sciences. Every article addresses at least two, if not several, critical topics: (i) development and mechanisms driving vocal control and modulation; (ii) cultural and other environmental factors affecting voice modulation; (iii) evolutionary origins and adaptive functions of vocal control including cross-species comparisons; (iv) social functions and real-world consequences of voice modulation; and (v) state-of-the-art in multidisciplinary methodologies and technologies in voice modulation research. With this collection of works, we aim to facilitate cross-talk across disciplines to further stimulate the burgeoning field of voice modulation. This article is part of the theme issue 'Voice modulation: from origin and mechanism to social impact (Part I)'.